Human resource practices, problems & solution of tour & travel agency business in Bangladesh: A study on Touristta Bangladesh - Saha, Shreya (Brac University, 2020)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters of Business Administration, 2020.